REFORMASI BIROKRASI DI KECAMATAN BUAHDUA KABUPATEN SUMEDANG (JRPA - Journal of Regional Public Administration, 2017)
Development Agenda Agenda for bureaucratic reform is one thing that gets special attention for the government. The Special Ministry that discusses bureaucratic matters, namely the Ministry of Empowerment of the State Apparatus and Bureaucratic Reform (PERMENPAN-RB). In the framework of carrying out the mandate of bureaucratic reform, Buah Dua Subdistrict, Sumedang Regency, approved in the Strategic Plan, Buah Dua Subdistrict (2014-2018: 2), was agreed to provide direction and reference for all components of the sub-district government, community and business world in order to realize their ideals and the objectives of the sub-district government are in accordance with the vision and mission as well as the direction of development that directs the policies of the Sumedang district government. Targeting is taken using the Sampling Technique, where the object is the District Head and Stakeholders with an interest in public service bureaucratic reform in Buahdua District. Based on the results of the study found the implementation of bureaucratic reform in the Buahdua sub-district has not been implemented very well, in fact the budget support for infrastructure to improve public services is very low, there is still something related to service information, Assessment To appreciate the vision and mission of the Buahdua sub-district. The obstacle that symbolizes bureaucratic reform, namely the organizational culture in Buahdua Subdistrict is still not conducive due to the involvement of the authorities, there is no proper honor for sukwan / award recipients who are very helpful in the process of public service, and every standard and complete SOP unit for the type services in their fields. Strategies to overcome obstacles to the implementation of bureaucratic reform in the Upper Buahdua Subdistrict, namely the DPRD must support proper respect for high performing religious workers by allocating to the APBD, Must provide space to the community through musrenbang, aspirations, must use service media.